Interconnected foams of helical carbon nanofibers grown with ultrahigh yield for high capacity sodium ion battery anodes. (October 2016) - Li, Mengya; Carter, Rachel; Cohn, Adam P.; Pint, Cary L.
Abstract: Here we demonstrate the growth of three-dimensional foams of defect-containing helical carbon nanofibers for application in efficient sodium ion battery anodes. Using pretreated Ni nanowire templates, over 3500% growth yield is observed for helical CNF foam materials, which can be directly incorporated into a sodium-ion battery anode. Our work demonstrates that the tortuous bends in helical CNFs provide a balance of nanodomains and defect sites that are responsible for high performance sodium storage. This includes sodium storage capacity exceeding 280 mAh/g at moderate rates of 100 mA/g with stable cycling performance over 200 cycles. Raman spectroscopic analysis during sodiation sheds insight into storage behavior of this material that confirms defect and nanopore mediated storage over the formation of an ordered intercalation compound. This work presents an intersection between the large-scale controlled growth science of carbon nanostructures and carbon materials optimized for efficient sodium storage applications.